Implementation of Financial Statement Presentation in Accordance with PSAK No. 1 in Restaurant Businesses in the City of Surabaya - Nisfatul Lailah; Diana Zuhro; Tjandra Wasesa; Sutini Sutini; Achmad Daengs GS; Enny Istanti; Indriana Kristiawati (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
The role of accounting in supporting the smooth execution of management tasks is very prominent, particularly in the planning and control functions. Accounting is able to provide financial information that is presented in the form of financial statements. Financial statements are considered fairly presented when they are prepared in accordance with the provisions of PSAK; the characteristics of such financial statements must be understandable, relevant, reliable, and comparable. In the preparation of financial statements, there are rules for recording transactions, which are known as the double-entry bookkeeping system. This system is commonly and widely used in the preparation of financial statements. However, financial statements in restaurant businesses in the city of Surabaya are prepared using a single-entry bookkeeping system. Theoretically, when financial statements are prepared using a single-entry system and the existing records do not show a complete summary of transactions, many specific difficulties will be encountered in preparing accurate financial statements. In addition, there is no direct way to determine whether the balances are correct, thus posing the risk of bias, inaccuracy, and misinterpretation, resulting in financial statements that do not comply with financial accounting standards. This condition motivated the author to conduct research on restaurant businesses in the city of Surabaya. In this study, the researcher restated the financial statements of restaurant businesses in Surabaya for the years 2023, 2024, and 2025 using the double-entry system, and presented them in accordance with the provisions of PSAK No. 1 concerning the Presentation of Financial Statements.